THE CRIME OF BRIBERY AND ITS IMPACT ON JOB PERFORMANCE - Al-Faraji, Naeem Maher Lafta (Antis Publisher, 2025)
Objective: This study explores the pervasive impact of bribery on societal and institutional integrity, emphasizing its role in eroding public trust and exacerbating social inequalities. Bribery undermines the very foundations of civil society, creating a system where the strongest and wealthiest individuals dominate. Method: The research utilizes a qualitative approach, examining the multifaceted nature of bribery across different levels of governance, from low-level officials to senior authorities. It analyzes the consequences of bribery on both individuals' rights and social cohesion. Results: The findings reveal that bribery is not only a localized issue but a transnational crime that spreads rapidly, posing a serious threat to social fabric and governance. The secrecy surrounding bribery deals makes enforcement challenging, limiting the effectiveness of legal countermeasures. Novelty: This study contributes by highlighting the systemic nature of bribery as a socio-political epidemic that requires a comprehensive, global response. It underscores the need for heightened awareness among public servants and the implementation of preventive measures to curb its damaging effects on society.